(untitled) (Journal of Advanced Research in Social Sciences, 2021)
The tumultuous China-Russia relationship looks back in time. The history of Chinese-Russian relations during the historical journey reflects the existence of two hostile forces that have developed a mutually beneficial cooperation in the shadow of an unsuccessful shared history, a cultural and racial bias of political misunderstandings, ideological differences and geopolitical competition. Although their relationship has been steadily improving during the 1990s to the present day, attitudes have remained highly ambiguous. Moscow and Beijing have reaffirmed their "strategic cooperation" and commitment to a new "global multipolar order," although senior Russian officials have continued to speak openly about the "Chinese threat". The passage from a constructive to a strategic Sino-Russian partnership took place along the historical path, based on a new cooperative vision that formed the cornerstone for the conciliation of the Chinese dragon and the Russian bear. The key question that emerges is the dynamics of this approach and its future. The development of China-Russia "strategic cooperation" can serve the following possibilities: strategic convergence, political and military alliance, the end of history, confrontation and strategic tension. As unique certainty, the relationship between these two countries traverses the emerging horizon, affects Eurasia and far beyond its limits, defining history’s route.